A computational tool to accurately and quickly predict 19F NMR chemical shifts of molecules with fluorine–carbon and fluorine–boron bonds. Issue 34 (19th August 2022) - Dumon, Alexandre S.; Rzepa, Henry S.; Alamillo-Ferrer, Carla; Bures, Jordi; Procter, Richard; Sheppard, Tom D.; Whiting, Andrew
Abstract : We report the evaluation of DFT-based procedures for predicting 19 F NMR chemical shifts for a range of molecules with fluorine bonds, to be used as a tool for the characterisation of reaction intermediates, products and mechanistic pathways. Abstract : We report the evaluation of density-functional-theory (DFT) based procedures for predicting 19 F NMR chemical shifts at modest computational cost for a range of molecules with fluorine bonds, to be used as a tool for assisting the characterisation of reaction intermediates and products and as an aid to identifying mechanistic pathways. The results for a balanced learning set of molecules were then checked using two further testing sets, resulting in the recommendation of the ωB97XD/aug-cc-pvdz DFT method and basis set as having the best combination of accuracy and computational time, with a RMS error of 3.57 ppm. Cationic molecules calculated without counter-anion showed normal errors, whilst anionic molecules showed somewhat larger errors. The method was applied to the prediction of the conformationally averaged 19 F chemical shifts of 2, 2, 3, 3, 4, 4, 5, 5-octafluoropentan-1-ol, in which gauche stereoelectronic effects involving fluorine dominate and to determining the position of coordination equilibria of fluorinated boranes as an aid to verifying the relative energies of intermediate species involved in catalytic amidation reactions involving boron catalysts.